PEMBERIAN PUPUK TRICHO KOMPOS JERAMI JAGUNG TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Agib Ginanjar; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Onion is one of the important commodity in Indonesia, onion is also a much-needed spice vegetables society. Onion crop growth is affected by the level of fertility of growing media and other environmental factors. Fertilization is vital to the growth and yield of onion for proper fertilization can increase the fertility of growing media. One effort to improve soil fertility mineral that is with organic matter. Organic materials that can be used is corn straw which has been decomposed with the help of the fungus Trichoderma sp. This study was conducted over three months from December 2014 to February 2015. The study was conducted experimentally with 5 treatment using a Completely Randomized Design (CRD), each treatment was repeated 4 times so that there are 20 experimental units. , Parameters measured were the number of leaves, number of tubers, tuber dry weight of the shelf, and wrap the tubers. Data were analyzed statistically and followed by Duncan's test at 5% level. The results showed that administration of tricho compost with a dose of 15 tonnes / ha gave the best results on the number of leaves, number of tubers and tuber dry weight of the shelf. Keywords: onion, Trichoderma sp, fertilization